Martin Oviatt papers - Oviatt, Martin
Three-volume diary (1863 May 3-1865 December 31) kept by Oviatt during his Civil War service with the Sixth Ohio Cavalry Regiment. Includes typewritten transcripts of the two volumes (1864-1865) prepared in 1995.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Union army soldier.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Army. -- Ohio Cavalry Regiment, 6th (1861-1865).; Ohio -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Soldiers